2005
DOI: 10.1007/s10661-005-6033-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting N and P losses from small catchments (Lithuania)

Abstract: Most of the important factors causing differences in nutrient losses and their interaction were analysed in three small catchments that are located in partially different geographic and climatic conditions in Lithuania. The investigation revealed that climatic factors change the amount and pattern of water discharge over year (larger water discharge during winter in the catchment located closer to the sea), but nutrient leaching is more dependent on land use. Agricultural factors, such as larger cultivated are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 16 publications
4
9
0
1
Order By: Relevance
“…The values predicted by the COUP model for N leaching losses after the application of mineral N fertilizer to perennial grass leys were in accordance with the low values measured, which ranged from 1.2 to 10-15 kg ha À1 yr À1 in Finland (Salo and Turtola, 2006) and in the Nordic-Baltic countries (References in Appendix B; Kutra and Aksomaitiene, 2003;Korsaeth et al, 2003;Sileika et al, 2005). Numerous studies demonstrated that N leaching losses from perennial grassland are inherently smaller than those from arable land, since N uptake covers a longer period and the soil normally remains untilled for at least three years, thereby reducing N leaching (Korsaeth and Eltun, 2000;Addiscott, 2005;Aronsson et al, 2014).…”
Section: N Balance and N Leaching Losssupporting
confidence: 75%
“…The values predicted by the COUP model for N leaching losses after the application of mineral N fertilizer to perennial grass leys were in accordance with the low values measured, which ranged from 1.2 to 10-15 kg ha À1 yr À1 in Finland (Salo and Turtola, 2006) and in the Nordic-Baltic countries (References in Appendix B; Kutra and Aksomaitiene, 2003;Korsaeth et al, 2003;Sileika et al, 2005). Numerous studies demonstrated that N leaching losses from perennial grassland are inherently smaller than those from arable land, since N uptake covers a longer period and the soil normally remains untilled for at least three years, thereby reducing N leaching (Korsaeth and Eltun, 2000;Addiscott, 2005;Aronsson et al, 2014).…”
Section: N Balance and N Leaching Losssupporting
confidence: 75%
“…Clearly, more studies on soils profiles and water tables in these ecosystems are required. The intensive land uses like overgrazing or high technology agriculture in the territory can transform vernal pools and marshlands into disturbed ponds edaphically characterised, as shown our results, by a high content in N as a consequence of cumulative effects in the catchments area (Sileika et al, 2005;Szajdak et al, 2006). The regression of vernal pool habitats, due to anthropic disturbance, affects the abundance of rare communities and species in a specific area; in particular, we can refer to I. setaceum.…”
Section: Discussionsupporting
confidence: 80%
“…The nutrients from the catchments are known to accumulate in wetlands (and lakes) that are known sinks (Mohanraj et al 2000). Among the nutrient elements under the study, P in particular is known to be adsorbed by soil particles and transported by erosion due to surface runoff (Sileika et al 2005). Hence, the differential water input to this wetland system could also be one of the reasons for high variability in the sedimentary nutrient content during some months.…”
Section: Discussionmentioning
confidence: 99%